Native Huts, Trinidad, B.W.I. - (:unkn) unknown (W.C. Ross and Co., Ltd., 2010)
A group of huts among coconut palms. Affixed to the postcard is a one dollar Montserratian postage stamp.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; [1930]; Thatched roofs--Trinidad and Tobago; Windows--Trinidad and Tobago; Wooden windows--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Ajoupa